Effects of Flavomycin, Bacillus licheniformis and Enramycin on Performance, Nutrient Digestibility, Gut Morphology and the Intestinal Microflora of Broilers - Hong L. Wang; Meng Shi; Xiao Xu; Long Pan; Pan F. Zhao; Xiao K. Ma; Qi Y. Tian; Xiang S. Piao (The Journal of Poultry Science, 2016)
The effects of Flavomycin, Bacillus licheniformis and Enramycin on broiler performance, nutrient digestibility, gut morphology and the intestinal microflora were studied in a 42-d experiment. A total of 288, one-day-old, male, Arbor Acres broilers were randomly assigned to 1 of 4 dietary treatments with 12 pens per treatment and 6 birds per pen. The treatments were comprised of a control diet without supplementation, a diet supplemented with 5 ppm Flavomycin, a diet supplemented with the combination of 5 ppm Flavomycin and 1.35×109 CFU/kg Bacillus licheniformis, as well as a diet supplemented with 5 ppm Enramycin. The average daily gain (ADG) and feed conversion ratio (FCR) of birds fed the diet with Flavomycin combined with Bacillus licheniformis and the Enramycin diet were improved (P<0.05) compared with the control diet. The digestibility of dry matter, energy, and calcium for birds fed the combination of Flavomycin and Bacillus licheniformis and the Enramycin diet were also enhanced compared with the control diet. All additives improved the villus height and crypt depth in the duodenum, jejunum and ileum on d 21. In addition, reduced numbers of cecal E. coli (P<0.01) were found in birds fed all three supplemented diets on d 42. In conclusion, supplementation with Flavomycin and Bacillus licheniformis in combination or Enramycin would appear to be superior to supplementation with Flavomycin alone. All three supplemented diets were superior to the control.